Method for Separating the Relative Contributions to the Emission Spectrum of Overlapping Luminescence Bands Presenting Different Dependencies on the Excitation Power - de Menezes, Leonardo S.; Galindo, Jefferson A.O.; Pessoa, Allison R.; Serge-Correales, York E. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Amaral, Anderson M. (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In many spectroscopic studies, complex luminescence spectra, resulting from a superposition of individual emission bands (EBs) originating from different excitation processes and/or relaxation pathways, commonly need to be analysed in detail. The usual method of separating these EBs relies on a quite arbitrary method, consisting of informing a multi-curve fitting algorithm about how many individual EBs should be found within the complex luminescence spectrum, defining peak positions by the naked eye and guessing their widths, also a quite inaccurate procedure. Very often it happens that the algorithm output is not robust against tiny variations of the input guesses, which naturally makes the analysis of the complex luminescence spectrum quite inaccurate and many times lacking physical reality.